(untitled) (VETERINARIA, 2021)
The bullhead - Cottus gobio Linnaeus, 1758 is the only species from the Cottidae family in Bosnia and Herzegovina and it inhabits the Una, Vrbas, Bosna, Drina river basins and the upper flow of the Neretva river. There are no reliable sources containing data on this species from this area. Threats that are most commonly caused by chemical water pollution have led to local extinction, and the range of the species is currently fragmented with numerous isolated populations. The aim of this study was to assess the interpopulation variability of selected morphometric parameters and fertility of bullhead from different sites of the Una and Drina rivers in Bosnia and Herzegovina. The results of this study indicate that there is no statistically significant interpopulation variability of morphometric parameters and reproductive performance of Cottus gobio species in the waters of Bosnia and Herzegovina. A significant influence of ecological factors on the reproductive potential of the species Cottus gobio was recorded, especially in females, where a negative correlation with water temperature was established. Research on this scientifically neglected species should certainly be continued with the aim of better understanding and elucidating the causes of its geographical specificity and variability.